Some aspects of squall over Indira Gandhi International airport, New Delhi - RAM, SURESH; MOHAPATRA, M. (MAUSAM, 2012)
A study is undertaken to analyse the characteristics of squall over Delhi and to find out the potential precursors for its prediction. For this purpose, the squall data of Indira Gandhi International (IGI) airport along with the surface and upper air meteorological parameters recorded by India Meteorological Department have been considered for all individual months over the period of 2001-2010. Apart from the characteristics like period of occurrence, intensity, duration, frequency and nature of squall, the environmental changes due to squall and thermodynamic features and indices leading to squall have been analysed. Higher than normal warming of lower troposphere upto 700 hPa level in March, April & June and at 925 hPa in May accompanied with cold dry air advection leading to lower than normal dew point in middle and upper levels (500-300 hPa in March, May and June, 400-300 hPa in April) are favourable for occurrence of the squall over Delhi. The lower level inversion in March and April only also helps in the occurrence of squall. In monsoon months of July- September, cold and dry air advection in middle and upper tropospheric levels (8- 15° C below normal dew point at 400-300 hPa in July, about 15° C below normal dew point at 300-200 hPa in August and 17- 24° C below normal dew point at 500-300 hPa in September) favours occurrence of squall over Delhi. Unlike pre-monsoon months lower level moisture does not play any role for the occurrence of squall over Delhi in monsoon months. Significantly higher than normal SWEAT index in March to September at 0000 UTC can be used as predictor of squall over Delhi on that day. Total totals index is the next suitable precursor for all the months except June.